MOBILE APPS: THE DUAL IMPACT ON EFL VOCABULARY MASTERY AND LEARNER AUTONOMY - Nurmayana Nurmayana; Linda Astuti Rangkuti; Nurhalimah Nurhalimah (Universitas Lambung Mangkurat, 2025)
Learner autonomy is a critical yet underdeveloped skill among Indonesian EFL students, who often exhibit a high dependence on teachers, particularly in vocabulary acquisition. This study addresses this gap by investigating the extent to which self-directed learning via mobile applications enhances both vocabulary mastery and learner autonomy. A mixed-methods design was employed, involving 20 undergraduate English education students who engaged in a three-week self-regulated vocabulary program using Quizlet and Duolingo. Data were collected via pre- and post-tests, an autonomy questionnaire, and semi-structured interviews.Quantitatively, the results demonstrated a significant improvement in vocabulary mastery (mean score rise from 56.3 to 72.5; p < 0.01). Notably, the strongest gains were observed in the contextual application of words, suggesting deeper processing facilitated by the mobile tools. The autonomy questionnaire further indicated substantial positive changes, with the overall mean score increasing from 3.1 to 3.9 on a five-point scale. The most pronounced growth was found in the sub-constructs of self-monitoring (3.0 to 4.0) and persistence (3.3 to 4.1). Supporting these numerical findings, interview data revealed that students highly valued the gamified motivation and the flexibility of learning, which fostered a sense of ownership. Challenges reported primarily related to internet instability and distractions.The study concludes that the systematic integration of mobile applications effectively enhances vocabulary acquisition while simultaneously cultivating key aspects of learner autonomy. These findings underscore the imperative for EFL educators to utilize mobile technology as a core resource for developing independent, self-regulated language learners..